Effect of Diet Supplementation with Combinations of Soybean and Linseed Oils on Milk Production and Fatty Acid Profile in Lactating Dairy Ewes - Antonacci, Liliana Elisabet (2018)
Thirty-six Pampinta ewes were used in a completely randomized design to examine the effectiveness of soybean (SO) and linseed (LO) oils to reduce the concentration of the atherogenic fatty acids (FA) of milk (C12:0 to C16:0) and increase the content of conjugated linoleic (cis-9, trans-11 C18:2) also called rumenic acid (RA) and vaccenic acids (trans-11C18:1, VA). Six ewes per treatment received a Control diet alone (71% alfalfa hay and 29% concentrate) or supplemented (0.24 kg/ewe·day) with pure oils (SO100 or LO100) or their blend at (%) SO75-LO25, SO50-LO50 and SO25-LO75. Milk yield, milk fat content and milk fat secretion were not affected. Milk protein content resulted higher in SO75-LO25, SO50-LO50 and SO25-LO75 without changes in milk protein yield. Total solid content of milk tended (p < 0.10) to increase after oil intake. Concentration of total atherogenic FA decreased and stearic, oleic and linolenic acids increased after oil intake. Milk content of VA and RA resulted higher in treatments with oils without differences between oil blends. The atherogenicity index (AI) in Control milk (2.23) was reduced (p < 0.001) by oil intake (1.15 to 1.37). The n-6/n-3 ratio averaged 7.27 in Control milk and was reduced (p < 0.001) by oils reaching a minimum value of 1.89 in LO100. Feeding polyunsaturated oils at 7% of total dry matter (DM) intake did not affect the productive response of dairy ewes resulting in an effective tool to improve the healthy value of milk fat. The SO50-LO50 blend showed the highest number of healthy changes in milk FA composition.